MENILAI KINERJA KEUANGAN MELALUI ANALISIS RASIO KEUANGAN PADA PT ANEKA TAMBANG TBK PERIODE 2018-2022 - Rafa, Wukuf Dilvan; Sastrawan, Rahman (JURNAL LENTERA AKUNTANSI, 2023)
This research was conducted to assess the financial performance of PT Aneka Tambang Tbk for the 2018–2022 period using financial ratios including liquidity ratios, solvency ratios, profitability ratios, activity ratios, and growth ratios. The research method uses descriptive-quantitative methods by collecting relevant data, such as company financial reports, for later analysis. The research results show that the financial performance of PT Aneka Tambang Tbk shows fluctuating results, such as the liquidity ratio, which is said to exceed the industry standard value, which means it can be said to be good. However, the solvency ratio shows that the calculation results exceed industry limits, which means it is not good in general even though there are good conditions in the 2022 period. The activity ratio also experiences a fluctuating situation where the 2018–2020 period is considered unfavorable, but in the 2021–2022 period, conditions are considered good. The latest analysis using the growth ratio shows that the company is far above industry standards and can be said to be very good. Key words: Financial Performance, Liquidty Ratio, Solvability Ratio, Profitability Ratio, Activity Ratio, Growth Ratio